2009
DOI: 10.1590/s1516-89132009000400025
|View full text |Cite
|
Sign up to set email alerts
|

Some Biochemical properties of polyphenoloxidase from spearmint (Mentha arvensis)

Abstract: Polyphenoloxidase (PPO; EC 1.14.18.1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
(68 reference statements)
1
7
0
Order By: Relevance
“…2b and c), ascorbic acid behaved similar to sulfides where it could reduce instantly the formed color and acted as quinone reducer. A lag period was reported before any observed increase in absorbance when ascorbic acid (Altunkaya and Gökmen 2008;Dincer et al 2002;Neves et al 2009) Fig. 3 UV-vis spectra of PPO assay under various conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b and c), ascorbic acid behaved similar to sulfides where it could reduce instantly the formed color and acted as quinone reducer. A lag period was reported before any observed increase in absorbance when ascorbic acid (Altunkaya and Gökmen 2008;Dincer et al 2002;Neves et al 2009) Fig. 3 UV-vis spectra of PPO assay under various conditions.…”
Section: Resultsmentioning
confidence: 99%
“…3 UV-vis spectra of PPO assay under various conditions. a absorbance of PPO assay at various periods, b catechol and ascorbic acid spectra at the assay concentrations, c adding ascorbic acid or cysteine after 10 min, and d adding citric acid at the beginning or after 10 min sulfites (Neves et al 2009) were used in PPO assays, which could be attributed to their reducing power toward quinone. Cysteine effect was also concentration dependent, it could also remove the developed color at higher concentrations (≥1.0 %) but its effect appeared after 120 s, not instantly as in sulfides and ascorbic acid, indicating its reactivity towards quinone but in a slower reaction rate.…”
Section: Resultsmentioning
confidence: 99%
“…The PPO showed the highest activity when pyrogallol was used as a substrate (100%), followed by 4-methyl catechol (67.44%), gallic acid (59.63%), catechol (33.71%), F I G U R E 2 Activity of POD and PPO as a function of substrate concentrations and Lineweaver-Burk plots using guaiacol as substrate for POD (a), H 2 O 2 substrate for POD (b), and pyrogallol for PPO (c) from pomegranate arils tyrosine (28.56%), and resorcinol (12.03%). PPO from various plant sources has been shown varying substrate specificity as reported in the literature (Aydemir, 2004;Dogan, Turan, Ertürk, & Arslan, 2005;McLarina & Leunga, 2020;Neves, Picchi, & Da Silva, 2009). POD reduces H 2 O 2 to water while oxidizing a variety of substrates (Nokthai, Lee, & Shank, 2010).…”
Section: Substrate Specificity For Pod and Ppomentioning
confidence: 91%
“…For l-tyrosine as a substrate the ph optimum of tyrosinase is 7.5. other authors (8,15) who studied the ph optimum of tyrosinase with different substrates and found values of pH = 6.0 for catechol, of pH = 5.0 for chlorophenol, of pH = 5.5 for r-cresol, of pH = 7.0 for phenol. The activity of the tyrosinase can be modulated by adding organic solutions such as isopropanol etc.…”
Section: Immobilization Of Hrp and Tyrosinase On Membranes Obtained Bmentioning
confidence: 97%